From the cave to Chinese Theater: cinema screen as a mirror of human drama - Sánchez-Escalonilla, Antonio (2022)
Film stories are usually associated with the evasion narrative or with entertainment genre, as a dramatic formula that eases disconnection with reality. If film was a mere illusion detached from real world we would have to accept the unreal nature of its characters as well as events told in their screenplay. Even though, our experience as spectators remembers us that, in multiple opportunities, films have constituted for us an object of reflection, of passionate debate or of sincere emotions. Because, as film maker and dramaturge David Mamet, “cinema is not a place where you go to forget, but a place where one goes to remember”. Following the director of State and Main we have to accept that films, as a narrative, offers to creative persons and spectators a direct reference to reality and the world that we inhabit. That is, the time we spend sited in front of a lightened screen is real time and belongs to our lives, it participates in the continuous formation of our personality and appeals in our vision of the world, originating empathy or rejection.